2011
DOI: 10.1190/1.3511524
|View full text |Cite
|
Sign up to set email alerts
|

Converted waves in a shallow marine environment: Experimental and modeling studies

Abstract: Seismic waves converted from compressional to shear mode in the shallow subsurface can be useful not only for obtaining shear-wave velocity information but also for improved processing of deeper reflection data. These waves generated at deep seas have been used successfully in hydrocarbon exploration; however, acquisition of good-quality converted-wave data in shallow marine environments remains challenging. We have looked into this problem through field experiments and synthetic modeling. A high-resolution se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In the first part of the study, source and receivers were kept at a constant distance of 3 m from the sea floor, sufficient to generate and acquire Scholte waves as shown in Kruiver et al (2010) and El Allouche et al (2011). The acquisition parameters allowed to vary were nearest offset (x 1 ), receiver spacing (∆x), spread length (x) and variation of depth of streamer, related to depth of sea floor.…”
Section: Methodsmentioning
confidence: 99%
“…In the first part of the study, source and receivers were kept at a constant distance of 3 m from the sea floor, sufficient to generate and acquire Scholte waves as shown in Kruiver et al (2010) and El Allouche et al (2011). The acquisition parameters allowed to vary were nearest offset (x 1 ), receiver spacing (∆x), spread length (x) and variation of depth of streamer, related to depth of sea floor.…”
Section: Methodsmentioning
confidence: 99%
“…In Allouche et al (2011) this is worked out theoretically; as a rule of thumb it can be said that a source and/or receiver must be within some quarter of a wavelength to the interface such that the exponentially decaying (evanescent) part of the arrival makes the amplitude not too small.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Examples of such waves have been reported in the past, like on land in global seismology (Daley & Hron, 1983) and in shallow land seismic (Roth & Holliger, 2000), called S* and a P S-wave respectively. Recently, such a non-geometric wave has also been discovered in a marine environment by Allouche et al (2011), where an evanescent P-wave in the water converts to a propagating S-wave in the water bottom. Its existence was shown by the use of OBC data and the modelling thereof.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Allouche et al (2010Allouche et al ( , 2011 have shown that these nongeometrically converted shear waves are clearly observable in data from a marine environment. They used data from water-bottom receivers in a shallow canal to demonstrate this statement, and they modeled seismic data to verify whether the observed response was consistent with the simulated response.…”
Section: Introductionmentioning
confidence: 99%